PENGARUH PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X DPIB SMK NEGERI 5 PADANG - Revi Syahira; Aima Zulfitri; Hafizah Delyana (Universitas Muhammadiyah Semarang, 2023)
This research is motivated by students' understanding of mathematical concepts is still low. The purpose of this study was to find out whether students' understanding of mathematical concepts by applying the Think Pair Share learning model is better than students' understanding of mathematical concepts by conventional learning in class X DPIB students of SMK Negeri 5 Padang. This research is a quasi-experimental research with a quasi-experimental design with a posttest only control group design with total sampling as research subjects. The sample of this research is class X students of SMK Negeri 5 Padang. This study used a final test instrument in the form of a description item with reliability = 0.54. The data analysis technique used is the t-test. Based on data collection techniques and data analysis performed tcount=2.28 and ttable=1.67 because tcount > ttable then the hypothesis is accepted, thus it can be concluded that student learning outcomes on students' understanding of mathematical concepts by applying the Think Pair Share learning model are better than student learning outcomes on students' understanding of mathematical concepts by applying conventional learning models.